Women in Panchayati Raj Structure in India: - (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The changing position of women in the Indian society has many facets as such generalization is nearly impossible because of the existence of a considerable variation between religions, rural and urban areas between classes and caste groups. Individuals differ in their cultural experiences. Migration to the urban areas, female political participation, education, the activities of social reformers and the inequalities of dowry enable women to make a relatively easy transition to new roles and responsibilities. Women are given leadership role in Panchayat Raj Institutions (PRIs) but their cultural experience shows that they learn to be docile and shy. However, it is with the help of formal and informal training, they would be able to accept the new roles and responsibilities. If the government is really serious in bringing the change then the third process of change that is freeing should be followed in which the concerned participant is given chance to show his/her abilities after having the proper training.